Implantación de un sistema contable en la empresa comercial Centro Ferretero de la ciudad de Loja, periodo abril a junio 2016 - Moncayo Guarnizo, Carmen María (2016)
The present work of thesis denominated "IMPLEMENTATION OF A SYSTEM ACCOUNTING IN THE BUSINESS COMMERCIAL CENTER FERRETERO OF THE CITY OF SHOP, PERIODO APRIL TO JUNE 2016", was raised with the purpose of applying accounting tools and procedures that help to have exact information and Ordinated on the economic and financial situation of the company, based on International Accounting Standards (IAS), the Generally Accepted Accounting Principles and the Internal Tax Regime Law. With the implementation, each of the specific objectives was accomplished, the first objective: To carry out the inventory of all the goods, values and obligations that the hardware has, so an initial physical inventory survey was carried out with the purpose of knowing the Assets and liabilities that the company possessed, being able to determine the values of the same through a cash register, checking accounts receivable and the respective revision of the current account statement and finally established the rights and obligations that it maintained with third parties, obtaining as a result The initial capital of the entity and the preparation of the respective State of Initial Situation; The second objective was to develop a plan and account manual to identify the economic and financial operations carried out in the Centro Ferretero Commercial Company. For this purpose, the plan and manual of accounts according to the activity of the company was established. Company, which is composed of a code, the account and its respective description facilitating the proper registration of the transactions; Consecutively the third objective was accomplished: to develop the control of the goods by the multiple account system, for their compliance was used several accounts of the system, in order to carry out the accounting of transactions related to purchases and sales Of goods; Finally, the fourth objective was to: Apply the accounting process for the preparation and presentation of Financial Statements that reflect the real situation of the Company, for its development was firstly to review and order the source documentation for the development of auxiliaries and Memorandum, which facilitated the recording of transactions in the Daily Book, Major General, Check Balance, Worksheet concluding with all Financial Statements that reflect the current situation of the company. Once the accounting process is applied, it is concluded that the practical application allowed to obtain real results through the Financial Statements, so it is recommended to implement accounting as an instrument that contributes to a better control of the operations that are carried out within the company.